Wood process domains and wood loads on floodplains. Issue 1 (15th December 2019) - Wohl, Ellen
Abstract: Downed large wood on floodplains creates similar geomorphic and ecological effects as wood in the active channel, but has been the subject of fewer geomorphic studies. I propose floodplain large wood process domains that are distinguished based on recruitment source at the reach to river‐length scale. Wood recruited to the floodplain can be autochthonous (individual or mass recruitment from floodplain forest), fluvially transported, or transported from adjacent hillslopes via mass movements that come down the valley side slopes or down the main channel. Fluvially transported wood can be further distinguished as being deposited: within the channel and subsequently accreted to the floodplain; marginal to the channel; on the floodplain during overbank flow; or on tributary fans. The mechanism of wood recruitment to a floodplain influences the spatial distribution of the wood across the floodplain and the proportion of wood pieces within jams, which in turn influences geomorphic and ecological effects of the floodplain wood. Using published studies of floodplain wood load for unmanaged river corridors, I hypothesize that the climate‐controlled balance between forest primary productivity and decay rates of downed wood is the first‐order control on floodplain large wood loads. Disturbance regime and wood recruitment mechanism are second‐order controls on wood load and primary controls on the spatial distribution of large wood. Understanding of floodplain large wood can be applied to quantifying the effect of large wood on river corridors; river restoration; paleoenvironmental inferences; and estimation of organic carbon stock in river corridors. © 2019 John Wiley & Sons, Ltd. Abstract : Floodplain large wood loads for unmanagedriver corridors reach maximum values in the temperate latitudes. This reflects the combined effects of forest primary productivity and rates of wood decay.